Impact of nitrate on the redox chemistry and solubility of Tc(IV) in alkaline, dilute to concentrated aqueous NaCl solutions. (November 2018) - Baumann, A.; Gaona, X.; Yalçıntaş, E.; Dardenne, K.; Prüßmann, T.; Rothe, J.; Duckworth, S.; Altmaier, M.; Geckeis, H.
Abstract: The impact of nitrate on the redox behaviour and solubility of 99 Tc(IV) was investigated in 0.1–5.0 M NaCl–NaNO3 –NaOH solutions with 0.1 M ≤ [NO3 − ] ≤ 1.0 M and 8.5 ≤ pHm ≤ 14.5 (with pHm = –log [H + ]) in the presence or absence of reducing agents (as Fe powder, Na2 S2 O4, Sn(II)). The evolution of the redox conditions as a function of time (for t ≤ 450 days) was investigated: (i) in the absence of technetium (inactive samples), (ii) in the presence of 99 Tc(IV) (added as 1–2 mg of TcO2 ∙0.6H2 O(am)), and (iii) in the presence of 137 Cs(I) (and absence of 99 Tc). All experiments were conducted in an Ar-glovebox (O2 < 1 ppm) at T = (22 ± 2) °C. An improved understanding of Tc redox processes in nitrate-rich alkaline solutions is relevant to predict Tc behaviour in specific nuclear waste disposal scenarios and a topic of fundamental scientific interest. Nitrate induces a clear increase in E h over time in the investigated aqueous solutions both in the presence and absence of reducing agents. In the case of Fe powder, this increase is observed almost immediately whereas in the presence of Na2 S2 O4 or Sn(II) the oxidizing effect is only observed after several months in inactive systems (absence of Tc). In the presence of technetium, the increase in E h occurs within a few days (5–50, depending upon reducing system, pHm and ionic strength). The evolution of E h in the presence of 137 Cs (with similar β – dose as in solubility experiments with 99 Tc) was analogous to that in the inactive systems. These observations indicate that the solid TcO2 ∙0.6H2 O(am) may play a role in catalysing nitrate reduction and radiation induced reactions have no significant impact in our experiments. Liquid-liquid extraction and XANES measurements confirm that technetium in the aqueous phase is mostly present as Tc(VII). Colorimetric nitrate/nitrite tests show the formation of nitrite, confirming that the oxidation of Tc(IV) to Tc(VII) is coupled to the reduction of nitrate. Our experimental observations support that, although kinetically hindered, nitrate can effectively oxidize Tc(IV). Highlights: Systematic solubility study with Tc(IV) in alkaline NaCl–NaNO3 systems. Nitrate induces the increase of E h in the investigated reducing systems. The increase of E h is accelerated by the presence of solid TcO2 (am, hyd). Very significant increase of Tc(IV) solubility observed with increasing E h . Solvent extraction and XANES confirm the predominance of Tc(VII) in solution.